Effect of Using Various Cathode Materials (Carbon Felt, Ni-Co, Cu-B, and Cu-Ag) on the Operation of Microbial Fuel Cell - Włodarczyk, Paweł; Włodarczyk, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Wastewater has high potential as an energy source. Therefore, it is important to recover even the smallest part of this energy, e.g., in microbial fuel cells (MFCs). The obtained electricity production depends on the process rate of the electrodes. In MFC, the microorganisms are the catalyst of anode, and the cathode is usually made of carbon material. To increase the MFC efficiency it is necessary to search the new cathode materials.
Keywords: bioelectricity; microbial fuel cell (MFC); bio-electro-chemical system; catalyst; cathode; environmental engineering; COD reduction; renewable energy sources